2006
DOI: 10.1111/j.1471-0528.2006.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational effects of preterm birth and reduced intrauterine growth: a population‐based study of Swedish mother–offspring pairs

Abstract: Objective To estimate the intergenerational effects of preterm birth and reduced intrauterine growth.Design Population-based cohort study.Settings Mother-first-born offspring pairs recorded in the Swedish Medical Birth Registry.Population Children born before 2001 to 38 720 women born in 1973-75.Methods The relationships between the mother's and the child's birth characteristics were estimated using logistic regression analysis. Adjustments were made for smoking habits, body mass index (BMI), and current and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 32 publications
7
68
0
5
Order By: Relevance
“…These findings are also in accordance with a previous study by Selling et al 71 , which found an intergenerational effect of mothers born SGA having a greater risk for delivering a SGA child. However, unlike this study we were able to establish that singleton women born preterm were more likely to deliver their own children both preterm or SGA.…”
Section: Intergenerational Effect Of Non--optimal Birth Characteristicssupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are also in accordance with a previous study by Selling et al 71 , which found an intergenerational effect of mothers born SGA having a greater risk for delivering a SGA child. However, unlike this study we were able to establish that singleton women born preterm were more likely to deliver their own children both preterm or SGA.…”
Section: Intergenerational Effect Of Non--optimal Birth Characteristicssupporting
confidence: 93%
“…In a previous study, on partly the same data as this thesis, on the heritability of preterm birth and intrauterine growth restriction among singletons, it was found that women born SGA were more likely to themselves give birth to a child born SGA or preterm 71 . A more recent study added knowledge on the heritability by showing that women born in a spontaneous preterm delivery were more likely to repeat this in their own pregnancies 72 .…”
Section: Heritability and Epigeneticssupporting
confidence: 52%
“…21 estimated that about 46% of the predisposition to be delivered SGA is due to genetic factors, with maternal and paternal components of 27.5 and 18.5%, respectively. Consistent with this recent research, SGA births tend both to cluster in families and to recur in successive generations, [22][23][24][25][26] even after adjustment for parental anthropometry and socioeconomic status.…”
Section: Introductionsupporting
confidence: 71%
“…1,2 Studies have shown the recurrence of preterm birth and low birthweight across generations. [3][4][5][6] So far, there have been relatively few studies on the impact of preterm birth and impaired fetal growth on later fertility, 7 the capacity to manage a successful pregnancy and perinatal outcome in offspring. A recent study found a significantly higher risk of perinatal death in offspring to mothers who were born very preterm or had a birthweight below 2000 g. 8 Multiple pregnancies were excluded from all of these intergenerational studies.…”
Section: Introductionmentioning
confidence: 99%